Congenital cytomegalovirus screening in neonates born after 35 weeks gestation—is targeted screening beneficial? - Aldon, Mary Liza; Raveentheran, Gayatiri; Amin, Zubair; Chan, Si Min; Aoyama, Rie; Tee, Nancy; Ng, Sau Yoke; Lee, Chun Kiat; Ng, Pick Gate; Low, Jia Ming (Frontiers in Pediatrics, 2025)
IntroductionCongenital Cytomegalovirus (cCMV) is the most common congenital viral infection and leading cause of non-genetic sensorineural hearing loss in children. Timely treatment within the first months of life can prevent hearing loss. We evaluated utility, feasibility, and short-term cost implications of targeted cCMV screening in a tertiary public healthcare institution in Singapore.MethodsWe analyzed data from neonates born at ≥35 weeks gestation from 1st February 2022 to 31st January 2023, at the National University Hospital, Singapore. Screening criteria for CMV testing were neonates who failed hearing screening at birth, had a birth weight <2.5 kg, small for gestational age (SGA), or had clinical suspicion for cCMV. Urine samples were obtained within two weeks of birth for CMV polymerase chain reaction (PCR) testing. We collected clinical, ophthalmological, neuroimaging, laboratory, and audiological data. A limited, short-term cost analysis was performed to compare costs of three cCMV screening strategies (universal, targeted, and no screening) two years after implementation.ResultsOut of 5,277 neonates, 305 (6%) met the screening criteria. Among those screened, 70.5% (215/305) were SGA or had a birth weight <2.5 kg, and 23.3% (71/305) failed the hearing screen. The overall diagnostic yield was 0.06% (3/5,277). There was one false positive result (0.3%; 1/305). Three neonates (0.98%; 3/305) were diagnosed with cCMV by urine PCR. One was SGA without intracranial abnormality, and two had low birth weight with intracranial calcifications. None had cytopenia or transaminitis, and all ophthalmology screenings were normal. All infected neonates were started on Valganciclovir. One neonate failed the hearing test at one month of age but passed repeat assessments by three months. Two neonates exhibited upper motor neuron signs in the lower limbs and are on long-term follow-up. The total estimated direct treatment-related cost without cCMV screening was S$104,445.79. In the targeted screening model, the total cost was S$146,656.30, compared to S$853,890.16 in the universal screening model.ConclusionWe demonstrated the feasibility of targeted cCMV screening, which complements universal newborn hearing screening in a tertiary neonatal center in Singapore. Targeted cCMV screening can be implemented cost-effectively during the neonatal period, enabling early detection and intervention.